2011
DOI: 10.1038/bmt.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

CsA 2-h concentration correlates best with area under the concentration–time curve after allo-SCT compared with trough CsA

Abstract: The relationship between CsA levels and area under the curve (AUC) in allo-SCT recipients, and the effect of age, concomitant use of steroid and MDR-1 polymorphism on this relationship remain largely unexplored. Steady-state CsA blood concentrations at time 0 (C0), 1 (C1), 1.5 (C1.5), 2 (C2), 3 (C3), 4 (C4), 6 (C6), 8 (C8) and 12 (C12) h post oral CsA dose were taken from 27 consenting allo-SCT recipients (receiving myeloablative or nonmyeloablative conditioning) at D 15 -D 25 (all participants) and D 40 -D 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…Therefore, C2 represents the optimal sampling time point which reflects the total systemic exposure (AUC) and consequently the optimal effect and adverse effect of the drug. Interestingly, the best correlations between C2 with AUC 0-12h and C2 with AUC 0-4h , in addition to the poor correlation of both AUCs with C0 found in the current investigation for bone marrow transplant Iraqi patients (Table 4) are similar to the results obtained in studies conducted in other nations and for different types of organ transplantation [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Parametersupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, C2 represents the optimal sampling time point which reflects the total systemic exposure (AUC) and consequently the optimal effect and adverse effect of the drug. Interestingly, the best correlations between C2 with AUC 0-12h and C2 with AUC 0-4h , in addition to the poor correlation of both AUCs with C0 found in the current investigation for bone marrow transplant Iraqi patients (Table 4) are similar to the results obtained in studies conducted in other nations and for different types of organ transplantation [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Parametersupporting
confidence: 84%
“…Interestingly, several articles demonstrated the best correlation between C2 and AUC 0-4h in different nations and for different types of organs allograft. Among these studies, were reported for lung transplantation [22], liver transplant recipients [24], heart transplantation [21,25], allogeneic stem cell transplantation [26], for children with idiopathic nephrotic syndrome [27], and for other types of organs transplantations [23,28]. The best correlation was also found between cyclosporine C2 level and AUC0-6hr for patients with corticosteroid resistant systemic lupus erythematosus [29].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have reported cyclosporine AUC in HSCT patients after i.v. administration [3,[10][11][12][13][14][16][17][18][19]26,27]. The method used to calculate or estimate cyclosporine AUC was not described in some of these reports [13], and serum rather than whole blood concentrations (the accepted standard matrix) were reported in another [10].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine dose adjustment based on AUC rather than C 0 has consequently become the standard of care. This approach has only just begun to be evaluated in HSCT [10][11][12][13][14][15][16][17][18][19]. Classical determination of AUC entails a large total blood sample volume, high workload to obtain the samples, high assay costs, and potentially a high level of patient inconvenience or distress.…”
Section: Introductionmentioning
confidence: 99%